2019
DOI: 10.5755/j01.eie.25.6.24827
|View full text |Cite
|
Sign up to set email alerts
|

Research on Big Data Mining Technology of Electric Vehicle Charging Behaviour

Abstract: Thousands of electric vehicles (EV), which are large in number and flexible in their use of electricity, will be connected to the power system in the near future, which will bring more uncertainty to the power system. Therefore, it is necessary to study the general characteristics of EV charging behaviours. In the charging process, big data regarding charging behaviour of EVs are generated. This paper proposes a big data mining technique based on Random Forest and Principle Component Analysis for EV charging b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Different approaches have been used to classify private charge behaviors, applying statistical analysis techniques [87,88], clustering [89,90], or data mining [91], substantially confirming the prevalence of slow night charging on weekdays. Using aggregate analysis of charging demand, one can gain insights into the charging behaviors of different types of users [92].…”
Section: Mobility and Charging Behavior Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Different approaches have been used to classify private charge behaviors, applying statistical analysis techniques [87,88], clustering [89,90], or data mining [91], substantially confirming the prevalence of slow night charging on weekdays. Using aggregate analysis of charging demand, one can gain insights into the charging behaviors of different types of users [92].…”
Section: Mobility and Charging Behavior Datamentioning
confidence: 99%
“…The third type concerns a wider range of factors, such as charging power, dwell time, and the cost of home charging [53]. Another study by Y. Liu et al [91] classified EV charging behavior during weekdays, weekends, and holidays for a month in 2018. The findings showed that the largest group of users recharged their EVs primarily during weekdays after dawn, with slow recharges and small amounts of energy.…”
Section: Classification Of Charging Behaviorsmentioning
confidence: 99%
“…In [86], regarding the movements of electric taxis as random walks, the Markov process is used to simulate the distribution of charging demand in static space, while in [87], the random forest (RF) method based on a regression tree is used to predict the driving characteristics of each EV, so as to obtain the travel mode data set of the EV. From the measured charging information and big data mining technology, the EV charging behavior model is presented based on RF and principal component analysis (PCA), which captures the EV with different charging characteristics based on a data-driven model [88]. The gradient boosting model (GBM) is used to simulate the SOC state at the end of a plug-in EV (PEV) daily schedule [89], and in [90], a generalized regression neural network (GRNN) is used to realize power prediction.…”
Section: Radial Basis Function [45]mentioning
confidence: 99%
“…The performance of unsupervised user behavior classification is improved by incorporating an adaptive generation strategy of initial clustering centers. The literature [10] divided the big data of charging behavior into three parts according to weekdays, weekends and holidays, and then used the random forest algorithm to perform multidimensional clustering respectively, and the results showed that the charging behavior of electric vehicles has certain regularity. The literature [11] clusters cities into five clusters based on electric bus data from 14 cities using the k-means algorithm for characteristic parameters such as charging power and charging time.…”
Section: Introductionmentioning
confidence: 99%